Ensaio sobre a genealogia, o ressentimento e o mestre ascético - Andrade, Leandro Antonio de (2016)
This work deals primarily with the possible relationships and differences between Nietzsche and Foucault, considering the philosophical tonic each, from the way they understand and use the genealogical method. Then it makes a detailed analysis of the concept of resentment and ascetic priest present in the Genealogy of Morals. Finally, presents some possible correlations between resentment and pastoral concept of power Foucault, in order to explore their psychological substrate, a possible genesis of religious institutions and the proposal of a new concept, the ascetic teacher who comes to pass the ascetic priest for the appearance of the teacher in middle age.